Maintaining recovery from alcohol use disorder during the COVID-19 pandemic: The importance of recovery capital. (1st December 2021) - Gilbert, Paul A.; Soweid, Loulwa; Kersten, Sarah K.; Brown, Grant; Zemore, Sarah E.; Mulia, Nina; Skinstad, Anne Helene
Abstract: Background: The potential impact of the COVID-19 pandemic on recovery from alcohol use disorder (AUD) has received scant attention to date. In response, we investigated the stability of recovery and identified correlates of relapse, with particular interest in differences between women and men. Methods: Data were obtained in a national survey of adults with resolved alcohol use disorder who were not drinking heavily (n = 1492). We calculated summary statistics and modeled odds of mild relapse (i.e., resolved at the time of data collection), overall and stratified by gender. Results: Equivalent large majorities of women and men reported that the COVID-19 pandemic had not affected their recovery at all (88.9% and 88.8%, respectively). Mild relapse events were infrequent, with only 45 participants (3.1%) reporting a resumption of drinking after being abstinent and 35 participants (2.7%) reporting an increase from previously moderated drinking, with no differences in prevalence between men and women. Recovery capital showed consistent and comparable protective effects for both women and men (adjusted odds ratio [aOR] 0.90; 95% confidence interval [95% CI] 0.84, 0.97; and aOR 0.93; 95% CI 0.88, 0.98, respectively). We did not find any effect of pandemic-related stressors; however, there were a number of distinct correlates of mild relapse for women and men. Conclusions: Recovery capital showed a consistently protective effect and may serve as a highly suitable intervention target as it is modifiable. Given gender differences, assessments of other key factors and tailored interventions targeting women and men may be necessary to ensure stable recovery. Highlights: Recovery appeared stable among our sample of adults not currently drinking heavily. Recovery capital was associated with lower odds of (mild) relapse. Early recovery was associated with greater odds of (mild) relapse. There were several other distinct risk and protective factors for women versus men.